"You can't read your way out of racism": creating anti-racist action out of education in an academic library. Issue 1 (7th December 2021) - Figueroa, Monica; Shawgo, Kristan
Abstract : Purpose: Under the transformational leadership of the University Librarian, University of North Carolina at Chapel Hill University Libraries shifted from having an education- and programming-based "diversity committee" to a council of librarians advocating for action, anti-racism and social justice, both within our organization and across campus. As our University Librarian noted, "you cannot read your way out of racism." Design/methodology/approach: With support from library leadership, the Inclusion, Diversity, Equity, and Accessibility (IDEA) Council has advanced anti-racism work in the libraries by serving as facilitators for a book discussion series, organizing a 21-day racial equity challenge, supporting staff in integrating anti-racism practices into their daily work through brown bag conversations, and facilitating the development of inclusion-focused performance management goals. Findings: What does an anti-racist library look like, and how does our organization envision this future? These questions anchor the IDEA Council's strategies. The libraries have witnessed a positive shift in staff participation: two-thirds of library staff participated in a Racial Equity Institute Groundwater presentation and in a library-wide book discussion series; approximately half the staff committed to our 21-day racial equity challenge. Participants were asked to reflect in conversation and through surveys. Originality/value: The first wave of a newly established grant program funded eight staff-led projects to advance social justice in the libraries. Additional steps included caucusing by racial identity, staff-wide discussions about racial equity, and a second wave of funding for the grant program. The authors approach this work with cultural humility: seeking to learn from one another, our peers and fellow activists.